Influence of Zr-metal-organic framework coupling on the morphology and photoelectrochemical properties of SnO2 - da Trindade, Letícia Guerreiro; Zanchet, Letícia; da Silva, Bianca Lins Zambon; Longo, Elson; Mazzo, Tatiana Martelli (Eclética Química, 2022)
In this work, we investigated the effect of the coupling of the Zr-metal-organic framework (MOF) and SnO2 and its potential for application as photoelectrode in solar cells. Coupling was performed by mechanical mixture followed by heat treatment. The effect of adding two amounts of Zr-MOF (25 and 50 wt%) on morphology and photoelectrochemical properties was investigated. The results of the J-V curves show that the coupling of 25 wt% Zr-MOF with SnO2 improved the charge transfer characteristics under light irradiated in 1.6 times compared to the pure SnO2.